Numerical simulation of functionally graded cracked plates using NURBS based XIGA under different loads and boundary conditions. (August 2015) - Bhardwaj, Gagandeep; Singh, I.V.; Mishra, B.K.; Bui, T.Q.
Abstract: In this paper, extended isogeometric analysis (XIGA) is performed to simulate the cracked functionally graded material (FGM) plates using first order shear deformation theory (FSDT) under different types of loading and boundary conditions. The gradation in material properties of the plate vary exponentially along thickness direction. The top and bottom surfaces of the plate are composed of ceramic and metal respectively. The properties of the equivalent composite are evaluated by rule of mixtures. The crack faces are modeled using Heaviside function, whereas the singularity in the stress field at the crack tip is modeled by employing crack tip enrichment functions. The domain integral approach is used for evaluating the stress intensity factor. The results obtained by XIGA for FGM plate are compared with equivalent composite plate.